Courting Justice: Tracing the Evolution and Future of Domestic Violence Courts. (July 2021) - Gover, Angela R.; Boots, Denise Paquette; Harper, Shannon B.
Specialized domestic violence courts (DVCs) have been a popular judicial option for processing domestic violence (DV) offenders since the 1990s. While DVCs vary in structure, common core components for programming have emerged across courts in the United States concerning courtroom features and processes. This article reviews the etiology and history of specialty courts for intimate partner violence, discusses the common programming components implemented by courts nationwide, and provides an assessment of the efficacy of DVCs in holding offenders accountable while simultaneously protecting victim safety. Finally, the article discusses the ongoing challenges and implications with regard to community response to DVCs.